Study of anemia in non-luminal solid tumors - Dandavate, Nupoor; Gadkari, Nitin; Rajbhoj, Ashwin; Patil, Mayur; Gaikwad, Naineesh; Bankar, Ashwin (International Journal of Advances in Medicine, 2023)
Background: Anemia is particularly prevalent in India due to widespread malnutrition. Cancer related anemia affects about three-fourths of cancer patients, causing symptoms like fatigue, appetite loss, and difficulty concentrating, and can worsen cancer prognosis, lengthen treatment, and reduce survival rates. Anemia is a significant cause of tumor hypoxia, which exacerbates the side effects of radiotherapy and chemotherapy, and affects energy levels and emotional distress. Methods: The present cross-sectional study aims to assess the prevalence and types of anemia in patients with newly diagnosed non-luminal solid tumors. The study sample included all patients meeting the inclusion criteria, with a sample size of 100. Clinical evaluation and investigations were carried out to determine the presence and severity of anemia. Data was compiled and analyzed. Results: Of the 100 patients enrolled, 68% had evidence of anemia, and the majority of them were in the age group of 51-60 years. Anemia’s association with body mass index (BMI) was noted and was more common in underweight and normal-weight patients. The commonest malignancies in the study were head and neck cancers, breast cancers and female genital cancers, and the incidence of anemia in these malignancies was higher than in other tumors. When sub-classified a higher prevalence in gynecological tumors was noted. The majority of anemic patients had mild anemia, with microcytic hypochromic anemia being the most common type. Conclusions: The study provides valuable information on the incidence and severity of anemia in patients with non-luminal solid tumors, which can help clinicians in their treatment planning and management.